Theory Z: Myths, Realities and Atlernatives - Mroczkowski, Thomasz (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
An assessment of substance and impact of Theory Z on American management in the context of alternative paths toward employee participation